2020
DOI: 10.2478/aiht-2020-71-3412
|View full text |Cite
|
Sign up to set email alerts
|

Cherry laurel fruit extract counters dimethoate-induced reproductive impairment and testicular apoptosis

Abstract: Dimethoate is an organophosphorus pesticide used against agricultural insects, which causes oxidative stress and damage in many organs, including the reproductive ones. Cherry laurel (Laurocerasus officinalis Roem.) fruit is rich in vitamins and phenolic compounds with antioxidant effect. The aim of this study was to investigate how effective its extract would be against dimethoate-induced testis and sperm damage in rats. Sixty animals were divided in six groups of 10. Group 1 (control) received only 1 mL of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Bakir et al. ( 2020 ) reported that cherry extract (Cherry laurel = Laurocerasus officinalis Roem.) was given to rats with damaged testicular tissue for 8 weeks‐maintained oxidant‐antioxidant balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bakir et al. ( 2020 ) reported that cherry extract (Cherry laurel = Laurocerasus officinalis Roem.) was given to rats with damaged testicular tissue for 8 weeks‐maintained oxidant‐antioxidant balance.…”
Section: Discussionmentioning
confidence: 99%
“…Bakir et al. ( 2020 ) reported that cherry extract (Cherry laurel = Laurocerasus officinalis Roem) given to rats with damaged testicular tissue for 8 weeks provided sperm DNA integrity. In this study, the corn gluten group significantly decreased the Bcl‐2 level when compared to the soybean meal and wheat gluten groups ( p < 0.05), indicating that the cells were more prone to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The same result was obtained by Sasi et al (2018b) and Sasi and EL-Ghoul (2021) . The possible reason for the effect of DM on the embryos may be attributed to alterations in sperm DNA of male mice treated with DM by overproduction of free radicals ( Navarro and Bustos, 2014 ; Bakir et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that DM has harmful effects on liver ( Heikal et al ., 2011 ; Saafi et al ., 2011 ; Al-Ali et al ., 2016 ), ovary ( Farag et al ., 2007 ), brain ( Astiz et al ., 2009 ), blood parameters ( Yasin and Sharma, 2013 ), the embryos ( Sasi et al ., 2013 ) and also induce DNA damage in mice bone marrow ( Ayed-Boussema et al ., 2012 ). Many studies have shown that male mice treated with DM caused a decrease in sperm motility and an increase in the percentage of abnormal sperm ( Jallouli et al ., 2015 ; Sasi et al ., 2018a , 2018b ), as well as structural alterations in testicular tissues ( Bakir et al ., 2020 ; Sasi and ELGhoul, 2021 ). The main objective of this study was to investigate the effect of the recommended dose of DM and its double on sex hormones, sperm morphology, and fertility in adult male mice.…”
Section: Introductionmentioning
confidence: 99%
“…In males, maternal exposure to DT disrupted the pituitary-testicular axis of mice neonates and inhibited steroidogenesis of adult mice [ 18 ]. Indeed, direct exposure to DT by oral administration reduced testicular weight and severely impaired sperm quality in mice [ 19 , 20 ] and rats [ 21 ]. At the cellular level, DT exposure also inhibited steroidogenesis [ 22 ] and differentiation of leydig cells [ 23 ].…”
Section: Introductionmentioning
confidence: 99%